Assistive learning technologies for learners with ADHD and ASD: – a review 2006-2016 - Andersen, Hanne Voldborg; Jensen, Rune Hagel Skaarup (Tidsskriftet Læring og Medier (LOM), 2019)
This literature review was a part of a research project investigating how technologies can be utilised to support learners with developmental and attention deficit to be included in mainstream learning contexts. The review contains research within the field of assistive learning technologies for learners with Attention Deficit Hyperactivity Disorder and Autism Spectrum Disorder from 2006 to 2016. The review is conducted, by using systematic and qualitative academically acknowledged literature search methods. Seven categories of technology-based interventions are recognised from current research, where technologies have been used to support: 1) memory disabilities and/or brain training, 2) increasing focusing attention, 3) time and task management, 4) communication, 5) reading, writing, language and literacy skills, 6) changing behaviour and 7) group work and collaboration. The results indicate that the overall findings of the rendered studies present mixed conclusions. The review calls for more research in a mainstream learning context with a universal design for learning approach.